Emotional freedom techniques for elderly patients with COVID-19: a case series on clinical recovery, frailty, and inflammatory biomarkers - Kemala Sari, Nina; Burhan, Erlina; Isbaniah, Fathiyah; Yennita, Dewi; Stepvia, Stepvia (Frontiers in Psychology, 2025)
Background/ObjectivesOlder adults are disproportionately affected by COVID-19 due to immunosenescence and comorbidities, resulting in higher rates of severe illness and mortality. Psychological distress such as anxiety and fatigue further compounds disease burden. Emotional Freedom Techniques (EFT), an integrative psychophysiological approach, has shown potential in enhancing psychological resilience and modulating inflammatory responses.MethodsWe report a case series of five elderly patients with confirmed COVID-19 admitted to Persahabatan Hospital, Jakarta. Each received standard pharmacological care, including antiviral therapy, corticosteroids, and comorbidity management, alongside daily EFT sessions combining acupressure, affirmations, and exposure techniques. Clinical symptoms, frailty status (via WHAS criteria), WHO Ordinal Scale for Clinical Improvement (OSCI), and serum IL-6 levels were monitored over a 30-day follow-up period. Emotional well-being was qualitatively assessed through follow-up interviews and therapist observations of patient engagement and affective behavior.ResultsAll patients demonstrated substantial clinical improvement. OSCI scores decreased from baseline values of 3–4 to 1 by the final follow-up, representing a 66–75% reduction in clinical severity. Frailty status improved markedly across all cases. IL-6 levels showed an average reduction of approximately 85%, suggesting a clinically meaningful improvement in systemic inflammation. No residual symptoms or adverse events were reported. Patients also demonstrated enhanced emotional well-being and adherence to EFT through digital guidance.ConclusionEFT may serve as a safe and supportive adjunct therapy in elderly COVID-19 patients, potentially accelerating clinical recovery and reducing inflammation and frailty. Further controlled trials are warranted to evaluate broader applicability in geriatric care.